Preliminary investigation of Late Pleistocene fauna from Ryonggok Cave No. 1, Sangwon County, North Hwanghae Province, Democratic People's Republic of Korea - Rye Sun Choe; Kum Sik Han; Se Chan Kim; Myong Hyok Ri; Jae Nam Ri (Journal of Quaternary Science, 2021)
The investigation of a limestone cave on the Ryonggok‐ri of Sangwon County, North Hwanghae Province, DPRK, has yielded many faunal remains including Late Pleistocene deer, brown bears and horses. Uranium series dating of fossil teeth yielded dates of ~72ka at the base of Layer 2 – the bone‐bearing unit – and ~44ka at the top. The rich and diverse mammal remains of Ryonggok Cave No. 1 are indicative of warm and humid temperate conditions during the Late Pleistocene, and reflect the presence of both dense forests and open grassland. In addition, pollen and spores from the site include two families and 24 genera of trees, six families and a genus of grasses and herbs, and two families and six genera of ferns, corroborating the environments inferred from the faunal remains.